High-utilization-rate compound feed for family pig farms - WANG ZHEN (2018)
The invention discloses a high-utilization-rate compound feed for family pig farms. The high-utilization-rate compound feed comprises the following raw materials in parts by weight: 30-40 parts of a yeast extract composite, 10-20 parts of palm kernel meal, 5-9 parts of rice bran meal, 8-16 parts of olea europaea cakes, 10-16 parts of yellow mealworm powder, 30-40 parts of glutinous millet, 20-30 parts of dehuked barley, 6-12 parts of rape, 10-16 parts of sesbania cannabina, 10-20 parts of fertile land radishes, 2-4 parts of Chinese herbal medicines, 1-2 parts of an immunopotentiation agent, 0.06-0.1 part of trace elements, 2-4 parts of maifan stone powder, 2-4 parts of calcium hydrogen phosphate, and 3-5 parts of table salt. The high-utilization-rate compound feed disclosed by the invention is favorable for healthy growth of live pigs, the period that the live pigs become full-grown and ready for slaughter is shortened, the breeding risks of a family pig farm are reduced, the economicbenefits are increased, t